Fodder tree and straw diets for sheep: Intake, growth, digestibility and the effects of phenolics on nitrogen utilisation - Reed, J.D.; Soller, H.; Woodward, A. (Elsevier, 1990)
A study was conducted to determine the intake, growth and digestibility in sheep fed forage produced from four African multi-purpose trees in combination with straw and the effects of poly-phenolics on noug cake and urea. Analyses content of nitrogen, neutral detergent fibre, acid detergent fibre, acid insoluble proanthocyanindins and indigestible neutral detergent fibre in four fodder trees, vetch hay, noug cake & teff straw. Presents data on apparent & true digestibility of organic matter, and digestibility of neutral detergent fibre and acid detergent feeds in combination with teff straw, and apparent & true digestibility of nitrogen, digestibility of nitrogen in neutral detergent fibre and nitrogen balance for sheep consuming seven feeds in combination with teff straw.